Research on Anti-Money Laundering Combating the Financing of Terrorism (AMLCFT) Supervision in Laos - SIPHADA, Vatthanaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
Recently, the problems of money-laundering (ML) and the financing of terrorism (FT) have threatened the social stability of the countries, affecting the financial system, the economy, society and so on. Therefore, many countries around the world including Laos have strongly focused on solving, preventing anti-money-laundering, and funding for the terrorist attacks, by handing closely cooperation and information exchange of each other. In this paper, we studied the situation of the anti-money-laundering and combating the financing of terrorism (AML/CFT) in Laos, and the strategies or tools used to cope with the money-laundering and financing of terrorism (ML/FT), including the regional and international cooperation of Lao PDR. This study is a qualitative study that uses secondary and description by describing patterns using tables and charts. The results of this study have found that the situation in terms of ML/FT in Laos is considered to be high risk in term of money-laundering. The level of corruption transparency is ranked 135th out of 180 countries, the form of ML is derived from drug trafficking and subsequently to human trafficking. The strategies and tools we currently have included specific units of the AML/CFT, laws improvement, decision, and recommendation, as well as regional and international treaties. However, it is not possible to meet the FATF standards, with most of its assessments at the NC level. Therefore, Laos should be encouraged to increase the knowledge and understanding of the issue of social change, the improvement of laws and policies, and to increase the effectiveness of international and regional cooperation more effectively.